PENGARUH STRUKTUR KEPEMILIKAN SEBAGAI MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERBANKAN - Henny Ritha (Jurnal Manajemen, 2019)
The financial crisis has raised questions about the finance institution’s Corporate Governance. Thisstudy analysed about the mechanism of corporate governance from the ownership structuresdimension and not from the managerial / control structures. This study was aimed at analyzing theeffect of ownership structure as the corporate governance’s mechanism on banking performance. Thevariables of ownership structure consisted of institutional ownership, managerial ownership, foreignownership, and public (society) ownership with Return On Asset (ROA) as the proxy of performancemeasurement. This study used sample which consisted of 19 banking companies that listed inIndonesian Stock Exchange in the period of 2011-2016. The analytical technique used to examine thehypotheses was multiple linear regression method. The results showed that institutional ownership andmanagerial ownership had an effect on banking performance, while foreign and public ownership hadno effect on banking performance.